RESTORING KNEE MOBILITY AFTER MENISCUS INJURIES: THE ROLE OF SURGICAL AND REHABILITATION TECHNIQUES - Mateusz Myśliwiec; Tytus Tyralik; Maciej Karwat; Julia Kular; Oliwia Malec; Justyna Niebylecka; Izabella Michalska; Natalia Glanc; Dominik Sendecki; Grzegorz Zalewski (International Journal of Innovative Technologies in Social Science, 2025)
Meniscal injuries are common knee joint conditions affecting both young, active individuals and older adults. The meniscus plays a key role in load distribution, shock absorption, proprioception, and joint lubrication. Modern treatment trends prioritize preserving the meniscus rather than removing damaged tissue. Clinical decisions depend on tear type, location, vascularity, patient age, activity level, and comorbidities such as osteoarthritis. This review, based on literature from PubMed, Web of Science, and Google Scholar, compares surgical and non-surgical strategies, focusing on outcomes, indications, and patient-specific factors. Arthroscopic meniscal repair (AMR) is favored for traumatic tears in younger, active patients, particularly those in vascular zones (red-red or red-white). Such injuries, often associated with anterior cruciate ligament (ACL) tears, yield better functional outcomes, reduced pain, and lower osteoarthritis risk with AMR compared to arthroscopic partial meniscectomy (APM). Results improve further when AMR is performed alongside ACL reconstruction due to enhanced healing conditions. In contrast, degenerative meniscal lesions (DMLs) - prevalent in middle-aged and elderly populations-respond poorly to surgery. Major trials (FIDELITY, ESCAPE) have shown no significant benefit of APM over structured physiotherapy or even placebo surgery. Moreover, APM may accelerate osteoarthritis progression and carries surgical risks. Consequently, guidelines recommend conservative management, including physiotherapy, exercise, and potentially intra-articular injections, as first-line treatment for degenerative tears. In summary, meniscal treatment should be individualized: surgical repair for young patients with repairable traumatic tears, and non-operative management for degenerative cases. Advances in biologics and imaging may further refine treatment approaches.